1994
DOI: 10.1128/iai.62.6.2582-2589.1994
|View full text |Cite
|
Sign up to set email alerts
|

Phase variation in pneumococcal opacity: relationship between colonial morphology and nasopharyngeal colonization

Abstract: When colonies of encapsulated isolates of Streptococcus pneumoniae are viewed with oblique, transmitted light on a transparent surface, they are heterogeneous in appearance because of variation in opacity. There is spontaneous phase variation among at least three discernible phenotypes at frequencies from 10-3 to 10-6. The ability to detect differences in opacity varies according to serotype, but variation is independent of capsule expression. Electron microscopy shows no difference in chain length but suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(203 citation statements)
references
References 45 publications
(44 reference statements)
8
189
0
6
Order By: Relevance
“…The recent discovery of an adhesive pneumococcal pilus provides one explanation why encapsulated pneumococci are capable of adhering to respiratory epithelial cells (Barocchi et al, 2006). It has also been demonstrated that pneumococci may undergo a phase variation where transparent, less encapsulated pneumococci are more apt to colonize the URT while opaque, more encapsulated variants are found in the bloodstream (Weiser et al, 1994;Kim and Weiser, 1998). In addition, capsule expression may be downregulated as a consequence of bacterial interactions with respiratory cells (Hammerschmidt et al, 2005).…”
Section: Figmentioning
confidence: 99%
“…The recent discovery of an adhesive pneumococcal pilus provides one explanation why encapsulated pneumococci are capable of adhering to respiratory epithelial cells (Barocchi et al, 2006). It has also been demonstrated that pneumococci may undergo a phase variation where transparent, less encapsulated pneumococci are more apt to colonize the URT while opaque, more encapsulated variants are found in the bloodstream (Weiser et al, 1994;Kim and Weiser, 1998). In addition, capsule expression may be downregulated as a consequence of bacterial interactions with respiratory cells (Hammerschmidt et al, 2005).…”
Section: Figmentioning
confidence: 99%
“…Further work is needed to clarify the immunological presentation of these antigens during natural infections. During carriage PiuA and PiaA are likely to be more accessible to exogenous antibody as the amount of polysaccharide capsule expressed during nasopharyngeal colonisation is less than in the bloodstream [35]. This could therefore favour PiuA and PiaA as upper respiratory tract mucosal antigens, for the elimination of pneumococci from the nasopharynx.…”
Section: Childmentioning
confidence: 99%
“…increased virulence in the blood stream, as was shown in mouse models of systemic disease (Briles and Tomasz, 1973;Weiser et al, 1994;Kim and Weiser, 1998;Gosink et al, 2000). Transparent variants invaded both human and rat BMEC more readily than opaque variants, and activation of BMEC with TNF-a resulted in increased invasion of both transparent and opaque pneumococci (Ring et al, 1998).…”
Section: Blood Brainmentioning
confidence: 84%
“…S. pneumoniae occurs in various phase variants such as opaque and transparent forms. Opaque variants contain more capsular polysaccharide relative to the ChoP containing cell wall teichoic acids, an increase in the amount of pneumococcal surface protein A (PspA), the pneumococcal autolysin LytA and a decrease in choline-binding protein (Cbp) A (also known as PspC), compared with transparent variants (Briles and Tomasz, 1973;Weiser et al, 1994;Kim and Weiser, 1998;Gosink et al, 2000). The opaque form has a reduced ability to colonize the nasopharynx but an HUVEC, human umbilical vein endothelial cells; A549, human nasopharyngeal epithelial cells; PAFR, platelet-activating factor receptor; TNF, tumour necrosis factor; IL, interleukin; BMEC, brain microvascular endothelial cells; PM, particulate matter.…”
Section: Blood Brainmentioning
confidence: 99%